Radiation refrigeration nano cellulose aerogel and preparation method thereof

By using the directional freeze-dried aerogel prepared with nanocellulose and polyvinyl alcohol, the problems of low refrigeration power and poor environmental adaptability of existing radiation refrigeration technologies are solved, and efficient heat insulation and radiation refrigeration effects are achieved, which are suitable for multiple A practical application scenario.

CN119505352APending Publication Date: 2025-02-25TIANJIN UNIV OF COMMERCE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411672059.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing radiation refrigeration technology has problems such as low refrigeration power, high dependence on atmospheric transparency, poor environmental adaptability, difficulty in large-scale manufacturing processes, and poor economic analysis.

Method used

Using nanocellulose (CNF) and polyvinyl alcohol (PVA) as the main raw materials, radiation-refrigerated nanocellulose aerogel with anisotropic structure was prepared by directed freeze-drying, which improves its thermal insulation ability, mechanical strength and Radiation cooling effect.

Benefits of technology

It realizes the low thermal conductivity of the aerogel (minimum 34.56mW·m-1·K-1), high compressive strength (maximum 291Kpa) and high cooling temperature (maximum 15℃), while reducing the impact on the environment. It is suitable for In the fields of cold chain logistics packaging and building energy conservation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505352A_ABST
    Figure CN119505352A_ABST
Patent Text Reader

Abstract

The invention discloses radiation refrigeration nanocellulose aerogel and a preparation method thereof, and belongs to the technical field of aerogel materials.The preparation method comprises the steps that polyvinyl alcohol, nanocellulose and / or borax serve as raw materials, N, N '-methylenebisacrylamide and methyl-trimethoxysilane are added, composite wet gel is obtained, the composite wet gel is directionally frozen, and the radiation refrigeration nanocellulose aerogel is prepared. The lowest heat conductivity coefficient of the radiation refrigeration nanocellulose aerogel can reach 34.56 mW.m <-1 >. K <-1 >, the highest compressive strength can reach 291 Kpa, and the highest cooling temperature can reach 15 DEG C. The aerogel is expected to be applied to the related fields of cold-chain logistics packaging, building energy conservation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aerogel materials technology, and particularly relates to a radiation-cooled nanocellulose aerogel and its preparation method. Background Technology

[0002] With the increasing severity of global greenhouse effect and climate change, energy conservation and green ecology are receiving growing attention. Due to large-scale population growth, rapid transportation, and urbanization, refrigeration is closely intertwined with daily life, widely used in building energy conservation, food preservation, transportation, and other fields. However, the most common refrigeration systems, built using vapor compression refrigeration, typically require significant energy consumption and generate substantial carbon dioxide emissions. By 2050, relevant organizations predict that this refrigeration demand will reach 5.8 EJ, with significant growth expected in Latin America, China, and India. Therefore, there is an urgent need to find new refrigeration strategies that balance energy conservation and environmental protection.

[0003] Radiation cooling technology is a novel cooling technology that enables objects to cool themselves spontaneously. Its principle is to transfer heat to the cold outer space in the form of thermal radiation through the mid-infrared atmospheric transparency window band of 8-13μm, thereby achieving cooling. While radiation cooling technology has great potential and advantages, it also has some drawbacks and challenges, mainly including: (1) Low cooling power and high dependence on atmospheric transparency: The inherent low energy density of radiation cooling technology means that a large deployment area is needed to meet the cooling capacity requirements. Furthermore, its effectiveness is affected by atmospheric transparency, especially under the influence of factors such as humidity, aerosols, and clouds. (2) Environmental adaptability issues: The application effect of radiation cooling technology varies greatly under different climatic conditions, especially in cold weather, where the continuous cooling effect does not meet people's actual needs. (3) Scalable manufacturing process: How to utilize existing industrial methods to produce radiation cooling materials on a large scale at low cost while considering material performance is key to realizing its commercial value. (4) Economic analysis: Currently, the cost of many related equipment and materials is still relatively high, which to some extent limits their widespread application. Challenges of integration into existing infrastructure: Integrating radiative cooling technology into existing infrastructure (such as buildings) presents challenges related to safety and performance standards, building codes, retrofitting costs, and maintenance expenses.

[0004] Currently, most of the radiation cooling materials studied are organic polymers or inorganic nanoparticles, such as polyvinylidene fluoride (PVDF), silicon dioxide (SiO2), and titanium dioxide (TiO2). However, they are often difficult to degrade and have a certain impact on the environment. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention proposes a radiation-cooled nanocellulose aerogel and its preparation method. Using nanocellulose (CNF) and polyvinyl alcohol (PVA) as main raw materials, an aerogel material with an anisotropic structure was prepared by directional freezing. This material exhibits good thermal insulation, mechanical strength, and radiation cooling effect. Experimental tests show that its thermal conductivity can reach as low as 34.56 mW·m. -1 ·K -1 The aerogel boasts a compressive strength of up to 291 kPa and a cooling temperature of up to 15°C. It holds promise for applications in cold chain logistics packaging, building energy conservation, and other related fields.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] One of the technical solutions of the present invention:

[0008] This invention provides a radiation-cooled nanocellulose aerogel with a honeycomb-like pore structure in the longitudinal direction and a parallel directional tunnel structure in the transverse direction.

[0009] The longitudinal thermal conductivity of the radiation-cooled nanocellulose aerogel is 37.51-42.82 mW·m. -1 ·K -1 The transverse thermal conductivity is 34.56-41.09 mW·m. -1 ·K -1 .

[0010] The second technical solution of the present invention:

[0011] The present invention also provides a method for preparing the radiation-cooled nanocellulose aerogel, wherein polyvinyl alcohol (PVA), nanocellulose (CNF) and / or borax are used as raw materials, and N,N'-methylenebisacrylamide (MBA) and methyl-trimethoxysilane (MTMS) are added to obtain a composite wet gel, the composite wet gel is directionally frozen, and then freeze-dried to obtain the radiation-cooled nanocellulose aerogel.

[0012] The method for directional freeze-drying of the composite wet gel is as follows: the composite wet gel is placed on a circular polytetrafluoroethylene (PTFE) substrate, the circular PTFE substrate is located on a cylindrical copper column, the cylindrical copper column is located in a container, the container is used to inject liquid nitrogen, the liquid nitrogen does not submerge the cylindrical copper column, and after the liquid nitrogen is injected, the composite wet gel is unidirectionally frozen by the unidirectional cooling drive of the cylindrical copper column.

[0013] Furthermore, the container is made of copper.

[0014] The aerogel prepared by directional freeze-drying in this invention exhibits a clearly arranged layered structure parallel to the freezing direction in the transverse direction. Ice crystals mainly grow in the longitudinal direction (freezing direction), forming honeycomb-like pores in the longitudinal direction and parallel directional tunnel structures in the transverse direction. At the same time, directional freeze-drying promotes the formation of parallel sheet structures of micro and nano structures, enhancing the mechanical strength of the aerogel.

[0015] Although nanocellulose possesses excellent mechanical properties, high specific surface area, and high aspect ratio, and is an environmentally friendly and renewable material, it also exhibits strong emissivity through atmospheric windows due to its abundant CO and C-OH groups. Therefore, this invention uses nanocellulose to prepare radiative cooling materials, which can reduce environmental impact. However, in practical applications such as cold chain logistics packaging and building energy conservation, it is necessary to improve its mechanical strength to further enhance its application value. In the preparation method of the radiative cooling nanocellulose aerogel of this invention, borax can be added or not. The addition of borax helps improve the mechanical strength of the aerogel, enabling it to be used in cold chain logistics packaging and building energy conservation. Simultaneously, this invention employs directional freeze-drying to prepare an aerogel material with an anisotropic structure. This material exhibits good thermal insulation, mechanical strength, and radiative cooling effect. Experimental tests show that its thermal conductivity can reach as low as 34.56 mW·m. -1 ·K -1 The compressive strength can reach up to 291 kPa, and the cooling temperature can reach up to 15°C. This invention, through dynamic design, allows the radiative cooling material to passively or actively improve thermal comfort according to environmental changes. Simultaneously, the aerogel of this invention can resist the effects of severe weather, and its performance is not affected under adverse weather conditions.

[0016] Furthermore, the preparation method of the radiation-cooled nanocellulose aerogel includes the following steps:

[0017] PVA was added to the CNF suspension and stirred for the first time to obtain the first suspension;

[0018] Borax was added to the first suspension, and after a second stirring, the pH was adjusted to be alkaline to obtain the second suspension.

[0019] MBA was added to the second suspension, and the mixture was stirred a third time. MTMS was added, and the mixture was stirred a fourth time to obtain a composite wet gel.

[0020] The composite wet gel is placed on a circular polytetrafluoroethylene mold, which is located on a cylindrical copper column. The cylindrical copper column is located in a container for injecting liquid nitrogen. The liquid nitrogen does not submerge the cylindrical copper column. After the liquid nitrogen is injected, the composite wet gel is unidirectionally frozen by the unidirectional cooling drive of the cylindrical copper column, and then freeze-dried to obtain the radiation-cooled nanocellulose aerogel.

[0021] The concentration of the CNF suspension is 1.0 wt.%; and / or

[0022] The mass ratio of PVA to CNF suspension is 1:1000.

[0023] During the first stirring, the stirring temperature is 100℃ and the stirring time is 0.5-3 hours.

[0024] The dry weight ratio of borax to CNF in the suspension is (0-3):5, meaning the mass ratio of borax to CNF in the suspension is (0-3):5. For example, the dry weight ratio of borax to CNF in the suspension can be 0:5, 1:5, 2:5, or 3:5. Adding different proportions of borax further allows for control of the mechanical strength of the aerogel.

[0025] During the second stirring, the stirring temperature is 90℃ and the stirring time is 10 minutes; and / or

[0026] The pH adjustment to alkaline is: adjust the pH value to 10.

[0027] The mass ratio of the MBA to the MTMS is 0.006:1.

[0028] During the third stirring, the stirring temperature is room temperature and the stirring time is 30 minutes.

[0029] During the fourth stirring, the stirring temperature was room temperature, and the stirring time was 2 hours.

[0030] Furthermore, the freeze-drying temperature was -78℃ and the time was 72 hours.

[0031] The third technical solution of the present invention:

[0032] The present invention also provides the application of the radiation-cooled nanocellulose aerogel in cold chain logistics packaging and / or building energy conservation.

[0033] Compared with the prior art, the present invention has the following advantages and technical effects:

[0034] This invention utilizes directional freeze-drying to prepare an aerogel material with an anisotropic structure. This material exhibits excellent thermal insulation, mechanical strength, and radiative cooling effect. Experimental tests show that its thermal conductivity can reach as low as 34.56 mW·m. -1 ·K -1 The compressive strength can reach up to 291 kPa, and the cooling temperature can reach up to 15°C. This invention, through dynamic design, allows the radiative cooling material to passively or actively improve thermal comfort according to environmental changes. Simultaneously, the aerogel of this invention is low-cost, can be mass-produced, and can withstand the effects of severe weather without affecting its performance. Attached Figure Description

[0035] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0036] Figure 1 This is a schematic diagram of the mold used for directional freeze-drying according to the present invention;

[0037] Figure 2 Field emission scanning electron microscope image of the aerogel prepared in Example 1;

[0038] Figure 3 Field emission scanning electron microscope image of the aerogel prepared for Comparative Example 1;

[0039] Figure 4 The compressive strength of the aerogels prepared in Examples 1-4;

[0040] Figure 5 A photograph of the device consisting of an insulating foam box and a frame wrapped in reflective aluminum foil;

[0041] Figure 6 The results show the radiation cooling performance characteristics of the aerogels prepared in Example 1 and Comparative Example 1. Detailed Implementation

[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0043] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0044] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0045] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0046] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0047] Unless otherwise specified, the room temperature in the embodiments of the present invention is 25±2℃.

[0048] All raw materials used in the embodiments of this invention were obtained through commercial purchase.

[0049] It should be noted that radiative cooling materials need to reflect most of the sunlight in the 0.3-2.5μm solar wavelength range to prevent sunlight absorption, while simultaneously emitting their own heat through the 8-13μm atmospheric window to achieve cooling.

[0050] In an embodiment of the present invention, the nanocellulose suspension is obtained by adding nanocellulose to water and stirring.

[0051] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0052] The technical solution of the present invention will be further illustrated by the following embodiments.

[0053] Example 1

[0054] (1) Add 0.1g PVA to 100g of 1.0wt.% CNF suspension and stir continuously at 100℃ for 1h to obtain the first suspension;

[0055] (2) Dissolve borax (the dry weight ratio of borax to CNF suspension is 2:5) in the first suspension, stir continuously at 90°C for 10 min, and then adjust the pH value to 10 to obtain the second suspension.

[0056] (3) Add 12 mg MBA to the second suspension at room temperature and stir for 30 min;

[0057] (4) Add 2g MTMS and stir continuously for 2h to obtain composite wet gel;

[0058] (5) A schematic diagram of the mold used for directional freeze-drying is shown below. Figure 1 As shown, the mold is made of copper, with a cylindrical copper pillar placed in the center. A gap for injecting liquid nitrogen is left between the cylindrical copper pillar and the container. The composite wet gel is placed on a circular polytetrafluoroethylene (PTFE) core, and then the circular PTFE core is placed on the cylindrical copper pillar. Liquid nitrogen is injected into the container, but the liquid nitrogen does not submerge the cylindrical copper pillar. A unidirectional freezing method using liquid nitrogen is used to create a vertical temperature gradient, causing ice crystals to grow preferentially from the bottom to the top (vertically), thus freezing the wet gel unidirectionally. The frozen wet gel is then placed in a freeze dryer and freeze-dried at -78°C for 72 hours to prepare a radiation-cooled nanocellulose aerogel, which is designated as D-CAQ-2.

[0059] Example 2

[0060] Same as Example 1, except that no borax was added, and the resulting aerogel is denoted as D-CAQ-0.

[0061] Example 3

[0062] Same as Example 1, except that the dry weight ratio of borax to CNF suspension is 1:5, and the resulting aerogel is designated as D-CAQ-1.

[0063] Example 4

[0064] Same as Example 1, except that the dry weight ratio of borax to CNF suspension is 3:5, and the resulting aerogel is designated as D-CAQ-3.

[0065] Comparative Example 1: Preparation of Aerogels using a Non-directional Freezing Method

[0066] (1) Add 0.1g PVA to 100g of 1.0wt.% CNF suspension and stir continuously at 100℃ for 1h to obtain the first suspension;

[0067] (2) Dissolve borax (the dry weight ratio of borax to CNF suspension is 2:5) in the first suspension, stir continuously at 90°C for 10 min, and then adjust the pH value to 10 to obtain the second suspension.

[0068] (3) Add 12 mg MBA to the second suspension at room temperature and stir for 30 min;

[0069] (4) Add 2g MTMS and stir continuously for 2h to obtain composite wet gel;

[0070] (5) The composite wet gel was first placed in a -20℃ environment for 48 hours and then taken out and placed in a freeze dryer for freeze drying at -78℃. The aerogel obtained in this comparative example was named ND-CAQ-2.

[0071] The aerogels prepared in Example 1 and Comparative Example 1 were scanned using field emission scanning electron microscopy (FE-SEM) to observe their microstructure. The FE-SEM image of the aerogel prepared in Example 1 is shown below. Figure 2 It can be seen that the aerogel prepared by the directional freezing method exhibits a honeycomb-like pore structure in the longitudinal direction and a parallel directional tunnel structure in the transverse direction. That is, directional freezing can enable the aerogel to form a highly ordered anisotropic microstructure. The field emission scanning electron microscope image of the aerogel prepared in Comparative Example 1 is shown below. Figure 3 It can be seen that the aerogel formed by non-directional freezing has a randomly arranged microstructure and is disordered in both the longitudinal and transverse directions.

[0072] Test Example 1: Thermal Conductivity Test

[0073] The thermal conductivity of the aerogels prepared in Examples 1-4 and Comparative Example 1 was tested using a thermal conductivity analyzer, and the results are shown in Table 1.

[0074] Table 1. Thermal conductivity (mW·m) of the aerogels prepared in Examples 1-4 and Comparative Example 1 -1 ·K -1 )

[0075]

[0076] Table 1 shows that the thermal conductivity of ND-CAQ-2 is lower than that of D-CAQ-2, indicating that, at the same borax ratio, directional freezing results in a lower thermal conductivity than non-directional freezing. The preferred dry weight ratio of borax to the nanocellulose suspension is 2:5. It can also be seen that D-CAQ-2, i.e., the aerogel prepared in Example 1, achieves the lowest thermal conductivity (34.56 mW·m). -1 ·K -1 ).

[0077] Test Example 2 Mechanical Property Test

[0078] The compressive strength of the radiation-cooled nanocellulose aerogels prepared in Examples 1-4 was tested using a universal testing machine (model HY-0580(DB), purchased from Shanghai Hengyi Precision Instrument Co., Ltd.) according to GB / T 1041. Figure 4 The compressive strength of the aerogels prepared in Examples 1-4 is shown. It can be seen that D-CAQ-2, that is, the radiation-cooled nanocellulose aerogel prepared in Example 1, can obtain the highest compressive strength (reaching 291 kPa).

[0079] Test Example 3: Characterization of Radiative Cooling Performance

[0080] The radiation-cooled nanocellulose aerogel prepared in Example 1 and the aerogel prepared in Comparative Example 1 were placed on a device consisting of a frame wrapped with a heat-insulating foam box and a reflective aluminum foil, and placed on an outdoor chair to study the temperature changes of the aerogels prepared in Example 1 and Comparative Example 1 under real sunlight. Figure 5 The device consists of a frame wrapped in insulating foam boxes and reflective aluminum foil. Figure 6 The results of the radiation cooling performance characterization of the aerogels prepared in Example 1 and Comparative Example 1 show that D-CAQ-2, i.e. the radiation-cooled nanocellulose aerogel prepared in Example 1, can obtain the best radiation cooling performance. The directionally frozen D-CAQ-2 has the lowest temperature distribution. The average temperature of D-CAQ-2 is about 9°C lower than that of the EPS (polystyrene foam) sample, about 3°C ​​lower than that of the ND-CAQ-2 sample, and about 15°C lower than that of the ambient temperature (EPE).

[0081] As can be seen from the above, this invention uses polyvinyl alcohol (PVA), nanocellulose fibers (CNF), and / or borax (sodium tetraborate decahydrate) as raw materials, and adds N,N'-methylenebisacrylamide (MBA) and methyl-trimethoxysilane (MTMS) for double crosslinking. It does not require complex nanostructures or engineering techniques, and has unique advantages in terms of raw materials, structural properties, and preparation process. The aerogel prepared by this invention exhibits excellent radiative cooling effect. The aerogel prepared by directional freezing in this invention displays a clearly arranged layered structure parallel to the freezing direction in the transverse direction. Ice crystals mainly grow in the longitudinal direction (freezing direction), forming honeycomb-like pores in the longitudinal direction and a parallel directional tunnel structure in the transverse direction. Simultaneously, directional freezing promotes the formation of parallel sheet structures of micro-nano structures, enhancing the integration of internal nanocellulose microbundles with protruding nanowires on the aerogel surface. The formation of this internal network structure is crucial for improving the mechanical properties of the aerogel.

[0082] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A radiation cooling nanocellulose aerogel, characterized in that: The pores are honeycomb-like in the longitudinal direction and parallel directional tunnel structures in the transverse direction; The longitudinal thermal conductivity of the radiative cooling nanocellulose aerogel is 37.51-42.82 mW·m -1 ·K -1 , the lateral thermal conductivity is 34.56-41.09mW·m -1 ·K -1 .

2. A method for preparing the radiation cooling nanocellulose aerogel according to claim 1, characterized in that: Using polyvinyl alcohol, nanocellulose and / or borax as raw materials, adding N,N'-methylenebisacrylamide and methyl-trimethoxysilane to obtain a composite wet gel, directionally freezing the composite wet gel, and then freeze-drying it to obtain the radiation cooling nanocellulose aerogel; The method for directional freezing of the composite wet gel is as follows: placing the composite wet gel on a circular polytetrafluoroethylene mold, the circular polytetrafluoroethylene mold is located on a cylindrical copper column, the cylindrical copper column is located in a container, the container is used to inject liquid nitrogen, the liquid nitrogen does not submerge the cylindrical copper column, and after the liquid nitrogen is injected, the composite wet gel is unidirectionally frozen through the unidirectional cooling drive of the cylindrical copper column.

3. The method for preparing the radiation cooling nanocellulose aerogel according to claim 2, characterized in that: The following steps are involved: Adding polyvinyl alcohol to the nanocellulose suspension and performing a first stirring to obtain a first suspension; Adding borax to the first suspension, performing a second stirring and adjusting the pH value to be alkaline to obtain a second suspension; adding N,N'-methylenebisacrylamide to the second suspension, performing a third stirring, adding methyl-trimethoxysilane, performing a fourth stirring to obtain a composite wet gel; The composite wet gel is placed on a circular polytetrafluoroethylene, which is located on a cylindrical copper column, which is located in a container, and the container is used to inject liquid nitrogen, which does not submerge the cylindrical copper column. After the liquid nitrogen is injected, the composite wet gel is unidirectionally frozen by the unidirectional cooling drive of the cylindrical copper column, and then freeze-dried to obtain the radiation cooling nanocellulose aerogel.

4. The method for preparing the radiation cooling nanocellulose aerogel according to claim 3, characterized in that: The concentration of the nanocellulose suspension is 1.0 wt.%; and / or The mass ratio of the polyvinyl alcohol to the nanocellulose suspension is 1:1000.

5. The method for preparing the radiation cooling nanocellulose aerogel according to claim 3, characterized in that: During the first stirring, the stirring temperature is 100° C. and the stirring time is 0.5-3 h.

6. The method for preparing the radiation cooling nanocellulose aerogel according to claim 3, characterized in that: The dry weight mass ratio of the borax to the nanocellulose suspension is (0-3):

5.

7. The method for preparing the radiation cooling nanocellulose aerogel according to claim 6, characterized in that: The dry weight mass ratio of the borax to the nanocellulose suspension is 0:5, 1:5, 2:5 or 3:

5.

8. The method for preparing the radiation cooling nanocellulose aerogel according to claim 3, characterized in that: During the second stirring, the stirring temperature is 90° C. and the stirring time is 10 min; and / or The pH value is adjusted to be alkaline as follows: the pH value is adjusted to 10.

9. The method for preparing the radiation cooling nanocellulose aerogel according to claim 3, characterized in that: The mass ratio of the N,N'-methylenebisacrylamide to the methyl-trimethoxysilane is 0.006:

1.

10. Application of the radiation cooling nanocellulose aerogel according to claim 1 in the field of cold chain logistics packaging and / or building energy conservation.

Citation Information

Cited By

  • Honeycomb structure and method for producing same

    WO2026186730A1